The exploration for an advertising campaign for St. Paul University Manila's music therapy program to entice parents of children with autism, ages 7 to 12 years old, to improve their social communication skills - Viriña, Juan Ignacio U.; Reyes, Mitzi Marie Aguilar (Quezon City College of Fine Arts, University of the Philippines, 2017)
St. Paul University Manila established their music therapy program and offered the course back in 2004. Because St. Paul University Manila is the first university to offer a music therapy program recognized by the Commission on Higher Education (CHED), the school experiences difficulty in enticing parents to enroll their children with autism. According to Asuncion (2016), the head music therapist of St. Paul University Manila, music therapy as an intervention for people diagnosed with autism is not yet that well known within the Filipino community. St. Paul University Manila also experienced difficulty in advertising their music therapy program due to their lack in manpower, especially in managing their creative and marketing strategies. Because they relied too much in advertising through word of mouth, they only received a handful of clients in return. Although music therapy is already widely used in foreign countries, it has yet to make its name as an acceptable means of therapy and intervention here in the Philippines.

Parents of children with autism in the Filipino community usually resolve to known therapies such as speech, physical, or occupational therapy. Though these therapies may address the basic needs of a child with autism, it is inevitable for the child to meander when these therapies do not coincide with the child's personal interest. Therefore, it becomes a tendency for these children to object these therapy sessions and they become uninterested. Because of this, parents ought to look for more therapists for their child and it becomes a cycle. There are many cases that these parents shift from one therapist to another because their children simply do not enjoy the intervention.

Therefore I propose to create an advertising campaign for St. Paul University Manila's music therapy program to entice parents of children with autism, ages 7 to 12 years old, for them to improve their social communication skills. With music therapy, children with autism can enhance their skills in social communication by exercising their creativity in a fun and learning experience. Music therapy is a flexible form of intervention because the children are free to be themselves, in which the program flow always depends on the child's musical interests, making it easier for them to learn. With that said, advertising this new and creative form of intervention will surely be suitable for those children with autism who are in need of a different kind therapy that ought to coincide with their interest in the fun experience.
Thesis (Bachelor of Fine Arts in Visual Communication)--University of the Philippines Diliman
Bibliography: leaves 164-165
Keywords: Autism in children; Echolalia; Music therapy; Acoustics